Gambaran Evaluasi Penilaian Mahasiswa Program Studi Pendidikan Dokter terhadap Lingkungan Pembelajarannya - Agustina Arundina Triharja Tejoyuwono; Ita Armyanti; Rangga Putra Nugraha (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2015)
Background: Medical science program Faculty of Medicine Tanjungpura University implements a Competency-Based Curriculum or in Indonesian called as Kurikulum Berbasis Kompetensi (KBK), corresponded to the Kurikulum Inti Pendidikan Tinggi III (KIPDI III). The curriculum is applied since academic year of 2005/2006 and has been evaluated into Curriculum of 2013 (Kurikulum 2013). Learning environment is the manifestation of a curriculum, so that the assessment of the environment in the institution of medical program is a part of the implementation of the evaluation of the curriculum. DREEM questionnaire (Dundee Ready Education Environment Measure) is one of the tools that are appropriate to measure the learning environment. This research aims to assess the students’ perception of the learning environment on academic year of 2013/2014.Method: This research is a descriptive study with cross sectional design, conducted to measure the learning environment in students of medical science program. The DREEM questionnaire was used as the measurement tool. This research was conducted in November 2013 at Faculty of Medicine Tanjungpura University, Pontianak, West Borneo.Results: The total score of the DREEM obtained in this research is 14,55/200, which shows that students considered the learning environment, including lecturers, social environment, learning process, academic achievement, and learning atmosphere as positive environment. The students assumed that the environment could still be improved by optimizing the resources.Conclusion: The students inferred that the learning environment could still be improved by optimizing the existing resources as well as getting support by the faculty and university administrators itself.